2008
DOI: 10.1017/s0022215108002065
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic properties of injected calcium hydroxylapatite: potential false positive findings on positron emission tomography

Abstract: As injectable calcium hydroxylapatite becomes more widely used, especially in the treatment of patients with a history of head and neck cancer, physicians should be aware it may cause a potentially misleading, false positive positron emission tomography finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Because of this reason, not only radiologists but also otolaryngologists should be aware of radiological changes produced by injection materials. Many other studies have well demonstrated radiological features of injection materials on tomographic studies, such as computed tomography (CT) and positron emission tomography (PET), but they reported only a few cases …”
Section: Introductionmentioning
confidence: 99%
“…Because of this reason, not only radiologists but also otolaryngologists should be aware of radiological changes produced by injection materials. Many other studies have well demonstrated radiological features of injection materials on tomographic studies, such as computed tomography (CT) and positron emission tomography (PET), but they reported only a few cases …”
Section: Introductionmentioning
confidence: 99%
“…2 With regard to the hypermetabolism associated with injection of a calcium hydroxylapatite filler, this can be a source of false-positive findings on PET. 3,4 We have also noted hypermetabolism associated with fillers other than calcium hydroxylapatite (Fig 2), suggestive of an inflammatory response that can be subclinical. The study of facial fillers is an evolving multidisciplinary field with many questions remaining to be answered.…”
mentioning
confidence: 81%
“…High-frequency ultrasound complemented with magnetic resonance imaging and leukocyte scintigraphy, allowed the distinction between infections, fibrosis, granulomatous inflammation, and product migration (Grippaudo, Di Girolamo, Mattei, Pucci, & Grippaudo, 2014). Calcium hydroxylapatite is radio-opaque and can be seen in normal radiographs (El-Halaby & Furtado Araújo, 2014); however, its injection may cause local hypermetabolism and thus be a source of false-positive findings in PET scans (Damrose, 2008;Feeney, Fox, & Akhurst, 2009). Conventional X-ray films, CT, and MRI techniques often allow different materials to be distinguished (Ginat & Schatz, 2013).…”
Section: Diagnosis Of Adverse Filler Effectsmentioning
confidence: 99%